(untitled) (Green Life Medical College Journal, 2025)
Introduction: Healthcare workers are prone to occupational hazard. The study was aimed to find out the occupational health hazards and safety practices among the auxiliary health workers of the Green Life Medical College and Hospital. Methods: A descriptive type of cross sectional study was carried on auxiliary health workers of Green Life Medical College and Hospital who were nurses and technologists. The study was conducted from October 2022 to December 2022 by face to face interviewing of nurses and technologist by pretested semistructured questionnaires. The study was conducted among 207 respondents. Convenient type of nonprobability sampling was done to collect the required information. The data was analyzed both manually as well as by computer based software name MS Excel. Results: According to the study, majority (75.8%) of the respondents had their official post as nurse while about 24.1% of them were technologist. Majority of the respondents (68.1%) were within the age group of 17 to 27 years. Among the respondents majority (51.6%) had diploma degree and 4.3% had master’s degree. Regarding the monthly income, majority (42.5%) had monthly income within range from 16,000 to 20,000 taka. Majority (90.8%) of the respondents heard about occupational health hazards. A majority (96.1%) had perception that Hepatitis B and C infection is caused by sharp cutting injury, about 88.4% of the respondents told yes about Tetanus. Furthermore, majority (82.3%) had Perception on acute Radiation sickness and about 98% heard about personal protective equipment. About 81.7% had perception that lead apron can prevent excessive radiation exposure. About 96.4% had perception that long working hours cause mental illness. Most of the respondents (71.4%) had work experience of less than 5 years but only 12.5% of them had work experience of 11 to 15 years. Most (91.7%) of the respondents’ daily working hours was 6 to 11 hours. About 63% had exposure to needle or sharp cutting injury. A vast majority (93.5%) of respondents sterilized their wounds by antiseptic. According to the respondents, 86.5% had stress for long working hours. About 90% wore disposable gloves while working with sharp instruments. Majority (83.5%) of the respondents used PPE when working in the laboratory. But about half (51.8%) of them did not use any lead apron during work with X ray machine. Among them majority (87%) did not use dosimeters on aprons during work with X ray machine. More than half (55.6%) of the respondents had received training on safety practices from hospital. About 75.1% agreed about supervision of wearing personal protective equipment. About 98.5% respondents told they used separate colored containers to dispose of medical waste. According to the respondents, about 68.5% had taken full dose of hepatitis B vaccine and about 74% had taken full dose of tetanus vaccine. According to the respondents about 10.6% had hypertension, 7.7% had drug allergy, 5.5% had skin disease as well as asthma and 3.3% had diabetes. Conclusion: The survey showed that most of the auxiliary health workers were generally well aware of occupational hazards and safety practices but still there are some unsafe practices. Strengthening the implementation of safety standards and proper supervision can cope with this situation. Journal of Green Life Med. Col. 2025; 10(2): 47- 51